Associations between maximum isometric strength and weightlifting performance in youth weightlifters - Soriano, M. A.; Flores, F. J.; Alonso-Aubín, D. A.; García-Sánchez, C.; Ceniza-Villacastín, J. A.; Jiménez-Ormeño, E.; Lama-Arenales, J.; Comfort, P. (The Journal of Strength and Conditioning Research, 2025)
The aim of this study was to explore the differences between the isometric start position pull (ISPP) and mid-thigh pull (IMTP) peak forces in youth weightlifters and their associations with weightlifting performance. Forty-six male and female youth weightlifters (age: 15.4 ± 1.3 years, height: 1.66 ± 0.91 m, body mass: 65.7 ± 10.0 kg, weightlifting experience: 2.5 ± 1.6 years) participated. Weightlifting performance was evaluated as the sum of the heaviest snatch and clean and jerk. Isometric start position pull and IMTP kinetics were calculated using a force plate. Weightlifting performance, ISPP, and IMTP were evaluated in 3 different sessions and were calculated in absolute, relative, and allometrically scaled forms. Paired samples t-tests were conducted to analyze the differences between the ISPP and IMTP. Pearson's r correlation coefficient was used to determine the relationship between weightlifting performance and the ISPP and IMTP. Fisher's r-z transformation was performed to determine the differences in the magnitude of correlations between the ISPP and IMTP with weightlifting performance. Statistical significance was set at p = 0.05. All subjects had a significantly (p < 0.001) lower performance when performing the ISPP compared with IMTP. Significant (p < 0.001) and strong correlations were found between ISPP and IMTP with weightlifting performance (r = 0.56-0.91). Weightlifting performance was more strongly associated with ISPP than IMTP, although only significant in the relative and allometrically scaled forms (z = 2.19, p = 0.01, z = 2.34, p = 0.01, respectively). The ISPP is highly associated with weightlifting performance in youth weightlifters and should be included in talent identification and development testing batteries.